Performance of water hyacinth for removal of organic and inorganic pollutants from industrial wastewater - Pavithra, Engitaravanan (2019)
Water quality deterioration is one of the major concerns in the world. Rapid industrial and commercial developments are causing tremendous pressure on the water resources. Speedy developments in the industrial sector at Gebeng area threaten the water quality of its two rivers and deteriorating the environmental condition of the areas. Phytoremediation can be defined as the efficient use of plants to remove, detoxify or immobilise environmental contaminants in a growth matrix through the natural biological, chemical or physical activities and processes of the plants. The objectives of this research was to identity the level of organic and inorganic pollutant in industrial wastewater for baseline information and to determine the effectiveness of water hyacinth plant to remove the pollutants contains in wastewater. In this study, the tests and experiments was held in the field level for in-situ data and in the Environmental Laboratory of Universiti Malaysia Pahang for ex-situ data. The wastewater was collected from the study area and was analysed to collect the water quality data. The industrial wastewater which has been collected was poured into the three different containers. All the three containers was treated with water hyacinth with different percentage of wastewater sample. The experiment was carried out for one month duration with average of 3 measurements for each percentage. The parameters that was tested are pH, DO, temperature, turbidity, BOD, COD, TSS, Ammoniacal Nitrogen, Chromium, Copper and Lead. The highest removal efficiency of BOD, COD, TSS, Ammoniacal Nitrogen, Turbidity, Chromium, Copper and Lead was 73.3%, 82.1%, 70.8%, 66.4%, 67.8%, 68.9%, 67.1% and 65.9%. So, 100 % sample with water hyacinth is more efficient compare to 70% sample with water hyacinth and 50% sample with water hyacinth on removing organic and inorganic pollutants in industrial wastewater. Hence, the results proved that phytoremediation using water hyacinth plant is suitable and effective to treat industrial wastewater.